SUPERVISI MANAJERIAL DAN DAMPAK KUALITAS LAYANAN BIMBINGAN KONSELING DI KABUPATEN MURATARA - Defriansyah, Dedi; Sumaerto, Sumaerto; Wahyudi, Edi (Fakultas Tarbiyah dan Keguruan UIN Ar-Raniry, 2024)
Abstract: This study aims to analyze the impact of managerial supervision on the quality of guidance and counseling (BK) services at SMP Negeri Maur, Musi Rawas Utara Regency, focusing on how supervision directly affects service effectiveness in supporting students' personal, social, academic, and career development. The research employs a qualitative triangulation method with interviews, observations, and document analysis involving BK teachers, the principal, and school management to obtain a comprehensive understanding of the role of managerial supervision. This method was chosen to ensure data validity through multiple perspectives. Findings reveal that managerial supervision at this school has yet to adequately support BK teachers in implementing programs aligned with national standards. BK teachers often act as